Sīrat-i ʻUmar ibn ʻAbdulʻazīz : yaʻnī, Ḥaz̤rat ʻUmar bin ʻAbdulʻazīz ke mufaṣṣal savāniḥ zindagī, aur unke ʻahd-i hukūmat ke mujaddadānah kārnāme - Nadvī, ʻAbdussalām (SAMP early 20th-century Indian books project, 1919)
On the life of ʻUmar d. 720, Caliph of Islam.